The Effects of Reflective Thinking Skill Promoting Based Learning and Instruction on Reflective Thinking Behaviors among Nursing Students - Chaisa, Pornpimol; Janwijit, Saichol (Journal of Education Studies, Chulalongkorn University, 2020)
This research aimed (1) to compare reflective thinking behaviors of nursing students pre and post attending the instructional management by promoting reflective thinking skills, and (2) to compare the reflective thinking behaviors of nursing students who post received the instructional management by promoting reflective thinking skills to regular teaching method. Twenty eight sophomore/2nd year nursing students, Boromarajonani College of Nursing Buddhachinaraj, in the experimental group 14 persons and 14 persons in the control group who registered in the Health problem 1 subject, were enrolled in the study by purposive sampling. This study was a quasi-experimental, two groups pre-test, post-test design research. The research instruments were the demographaic data and Reflective Thinking Behaviors Assessment Form. The demographic data were analyzed by using frequency and percentage. The reflective thinking behaviors scores before and after attending the instructional management by promoting reflective thinking skills were compared by using paired t-test, and compared the reflective thinking scores of the control and the intervention group by using independent t-test. The results of the study showed that (1) the nursing students’ reflective thinking behaviors scores after attending the instructional management by promoting reflective thinking skills were higher than those before attending the instructional management method with statistical significance of .05, and (2) the reflective thinking behaviors scores of nursing students who received the instructional management by promoting reflective thinking skills were higher than those in the control group with statistical significance of .05.